2016
DOI: 10.12659/msm.894829
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Correlation Between APOM rs805296 Polymorphism and Risk of Coronary Artery Disease

Abstract: BackgroundThe present meta-analysis aimed to summarize the inconsistent findings on the association of apolipoprotein M gene (ApoM) rs805296 polymorphism with the risk of coronary artery disease (CAD), and to obtain a more authentic result about this topic.Material/MethodsA total of 7 available articles were identified through electronic databases – PubMed, EMBASE, and Chinese National Knowledge Infrastructure (CNKI) – and their useful data were carefully extracted. The relationship between ApoM rs805296 polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…28,29 Apolipoprotein M has also been studied for its role in other cardiovascular diseases including coronary artery disease, where low levels of ApoM were associated with high risk of disease development. 27,33 One possible explanation for the difference between our results and other’s findings could be the difference in nature of the diseases under investigation. Now it is well established that primary and recurrent VTE are 2 different diseases and their risk markers are not similar.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…28,29 Apolipoprotein M has also been studied for its role in other cardiovascular diseases including coronary artery disease, where low levels of ApoM were associated with high risk of disease development. 27,33 One possible explanation for the difference between our results and other’s findings could be the difference in nature of the diseases under investigation. Now it is well established that primary and recurrent VTE are 2 different diseases and their risk markers are not similar.…”
Section: Discussioncontrasting
confidence: 93%
“…23,24 Studies have shown that genetic aberrations in ApoM that affect the expression levels are associated with higher risk of coronary artery disease and diabetes mellitus. 25 27 Recently, genetic aberrations in ApoM have been shown to be associated with high risk of VTE recurrence in males. 28 Similarly, in a study by Memon et al, lower plasma levels of ApoM were associated with an increased risk of VTE recurrence in male patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the genotype frequency and distribution difference of rs805297 (C-1065A) and rs9404941 (T-855C) inindividuals with T2DM and healthy controls was not significant. Xu et al 11 . suggested that ApoM rs9404941 (T-855C) predicts highincidenceof CAD 8 .…”
Section: Discussionmentioning
confidence: 99%
“…In a few studies on human subjects presenting this mutation, there is an association with an increased risk of CVD. While most of these studies are underpowered, the collective conclusion in a meta-analysis of the results showed an increased risk of CVD and suggested that low levels of apoM caused by rs805296 may be a risk factor for CVD [56]. Importantly to remember, a study on the general Danish population was not able to identify any associations between plasma apoM and the risk of CVD [33].…”
Section: Apom/s1p Atherogenesis and Cvdmentioning
confidence: 99%